Aromatic amines equilibrium sorptive interaction with synthesized silica based mesoporous MCM-41: Physicochemical evaluation and isotherm modeling. Issue 4 (21st March 2019) - Toor, Sehaspreet Kaur; Kushwaha, Jai Prakash; Sangal, Vikas Kumar
Abstract: Present study reports the adsorption of aromatic amine, 4-chloro- o -toluidine (4-COT), onto synthesized mesoporous Mobil Composition of Matter No. 41 (MCM-41) silica nanoparticles, in batch mode. Synthesized MCM-41 was characterized by XRD, BET, FTIR, SEM and TEM analysis. The effects of pH, MCM-41 dose, 4-COT concentration, contact time and temperature were studied, and interaction of 4-COT with the surface of MCM-41 and adsorption process controlling mechanism were investigated. BET analysis of MCM-41 showed 502.77 m 2 g –1 of surface area. Kinetic experimental data were well represented by the pseudo-second order kinetic model. Freundlich and Temkin isotherm models well represented the adsorption equilibrium isotherm data.